Reassessing Guanxi as Social Capital: Boundary Conditions for Service Innovation and Productivity Growth - Jia, Li; Keoy, Kay Hooi (International Review of Management and Marketing, 2026)
Guanxi is widely regarded as a strategic form of social capital in emerging markets; however, its effectiveness in supporting internal capability development and sustaining productivity-oriented service innovation remains debatable. This study examines the boundary conditions under which guanxi influences service innovation implementation (SII) and organizational performance. Using partial least squares structural equation modeling (PLS-SEM) on survey data collected from 546 practitioners, the findings reveal a significance–relevance paradox. While Guanxi demonstrates a statistically significant moderating role in the relationship between organizational drivers and SII, its practical relevance diminishes within institutionalized and standardized operational contexts. Moreover, Guanxi does not significantly enhance individual service consciousness, indicating limited influence on employee-level cognitive and behavioral foundations essential for productive work practices. The results suggest that although Guanxi remains effective in facilitating external resource coordination, it serves as a weak complementary mechanism for managing internal service processes critical to sustained productivity growth. By clarifying the limits of guanxi as social capital, this study contributes to the management and marketing literature by advancing understanding of relational mechanisms in service innovation. The findings offer practical implications for managers in emerging economies seeking to balance relational strategies with formal organizational systems to promote service innovation, decent work, and long-term economic performance in line with Sustainable Development Goal 8.